Diagnostic accuracy of conventional, digital and Cone Beam CT in vertical root fracture detection - Valiozadeh, Solmaz; Khosravi, Maryam; Azizi, Zeynab (Iranian Endodontic Journal, 2011)
INTRODUCTION: Vertical root fracture (VRF) is a common failure in endodontically treated teeth. Due to VRF’s poor prognosis, a reliable and valid detection method is critical for treatment planning. Conventional and digital radiographs are limited in VRF detection. Recently, Cone Beam CT (CBCT) system has been introduced. This study aimed to compare the diagnostic accuracy of these three imaging modalities for VRF detection. MATERIALS & METHODS: One hundred and twenty extracted single-rooted teeth were selected and sectioned through cementoenamel junction. The roots were divided in two groups; group one consisted of 60 teeth with induced root fracture and group two had 60 teeth with no fracture. In the first group the crack was made by instron system. All samples were imaged by the three imaging modalities. Diagnostic accuracy was then compared with methylene blue dye detection method. Kappa was used for statistical analysis. RESULTS: CBCT showed the highest sensitivity (94.6%) and specificity (98.2%). Conventional radiography and digital radiography were not as accurate as CBCT. <span style="font-style: normal; font-family: ";Cambria";,";serif";; color: #595959; font-size: 10pt; mso-fareast-font-family: ’Times New Roman’; mso-fareast-language: ZH-CN; mso-bidi-language: FA; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US;">CONCLUSION: According to our study, CBCT seems to be better than conventional and digital radiography in detecting VRF and provides the most reliable data in comparison with the two other modalities.